1997
DOI: 10.1046/j.1365-2672.1997.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sites of injury in Lactobacillus bulgaricus during heat stress

Abstract: P. TEIXEIRA, H. CASTRO, C. MOHÁ CS I-F AR KA S AN D R . KI RB Y . 1997. Heat resistance of Lactobacillus bulgaricus in skimmed milk at 62°, 64°, 65°and 66°C was studied. The response to increasing temperatures in this range was not linear, with temperatures at 65°C and above giving a lower survival rate than would be predicted from experiments at lower temperatures. To identify sites of injury at these temperatures, chemical markers were used. Heating at 64°C and below resulted in damage to the cytoplasmic mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 12 publications
3
82
0
3
Order By: Relevance
“…The heating menstrum used was heat-treated (90°C, 30 min) 20% (wt/vol) RSM supplemented with 0.5% (wt/vol) yeast extract; an additional 1% (wt/vol) sucrose was added for strain UCC 118. The heating method used was essentially the method described by Teixeira et al (35). Two 50-ml portions of RSM in 100-ml bottles were agitated with magnetic stirrer bars and were placed in a water bath at the following test temperatures: 37°C (for the control and to obtain the initial count) and 55, 58, 59, 60, and 61°C.…”
Section: Methodsmentioning
confidence: 99%
“…The heating menstrum used was heat-treated (90°C, 30 min) 20% (wt/vol) RSM supplemented with 0.5% (wt/vol) yeast extract; an additional 1% (wt/vol) sucrose was added for strain UCC 118. The heating method used was essentially the method described by Teixeira et al (35). Two 50-ml portions of RSM in 100-ml bottles were agitated with magnetic stirrer bars and were placed in a water bath at the following test temperatures: 37°C (for the control and to obtain the initial count) and 55, 58, 59, 60, and 61°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, most probiotic strains do not survive well the high temperatures and dehydratation during the spray-drying process. Loss of viability is principally caused by cytoplasmatic membrane damage although the cell wall, ribosomes and DNA are also affected at higher temperatures [74]. It was reported that the stationary phase cultures are more resistant to heat compare to cells in exponential growth phase [61].One approach used by a number of researchers to improve probiotic survival is the addition of protectants to the media prior to drying.…”
Section: Spray-dryingmentioning
confidence: 99%
“…During these processes, bacteria are subjected to adverse conditions, one of the most encountered and drastic stresses being the heat stress. The bestdescribed effects induced by high temperatures concern the protein denaturation [28], but membranes, nucleic acids and certain enzymes have been equally identified as cellular sites of heat injury [25]. Heat stress is also responsible for a disturbance of the transmembrane proton gradient, leading to a decrease of the intracellular pH [21,22,29].…”
Section: Introductionmentioning
confidence: 99%